Implementación de la contabilidad en el hotel “KARINA” del cantón Macará, provincia de Loja. Periodo del 01 de septiembre al 31 de diciembre del 2017 - Saquicela Sanmartín, Andrea Rosario (2019)
The thesis work entitled IMPLEMENTATION OF ACCOUNTING IN THE HOTEL "KARINA" DEL CANTÓN MACARÁ, PROVINCE OF LOJA. PERIOD FROM 01 SEPTEMBER TO DECEMBER 31, 2017, was established with the purpose of developing the implementation of accounting according to the needs of the company to facilitate the control of its operations, thereby allowing a maximum optimization of its resources aimed at aggrandizement of this company. Also know in an effective way the economic situation that will provide the financial statements so that its owner can make the right decisions. It focused on the development of specific objectives in which: A plan and manual of accounts according to the services provided by the Hotel where the operating accounts were determined such as; Inventory of Foods and Beverages, Lodging services, sale of beverages and food, which allowed obtaining an order and efficient control of transactions and operations, which was carried out during the accounting process. Subsequently the initial inventory was made through physical verification of the assets, rights and obligations of the Hotel, in which it was determined that the building account has the most representative value since the owner has its own infrastructure for the provision of the service. Then the Initial Situation Statement was made, in which the Asset, Liability and Equity accounts are detailed. 6 Auxiliary records of sales and purchases were designed and developed with the purpose of chronologically recording the different operations carried out by the Hotel, whose procedure facilitated the recording of accounting entries in the Daily Book, General Ledger, Verification Balance. Finally, the accounting process was developed, resulting in financial statements that reflect the real economic-financial situation of the Hotel, such as the Income Statement, the Statement of Financial Position, the Cash Flow Statement and the Financial Statements. Finally, the respective conclusions and recommendations were established and presented. At the end of this work it was possible to highlight the positive aspects of accounting in this type of service companies, which although small, still need accounting tools to help their owners carry out their activities not empirically if not correctly through a adequate accounting control and obtain financial information that allows them to take fruitful measures for their economic development and improvement in the hotel area.